Optimization of the synthesis of highly pure calcium sulphate from dolomite ore - Isaac Adekunle Joseph; Elijah Olawale Ajala; Amina Ahmed El-Imam; Mary Adejoke Ajala; Comfort Temitope Are; Esther Olubunmi Babatunde (Scientific Reports)
Abstract This study explores the synthesis of calcium sulfate (CaSO4) from dolomite. The process involves leaching dolomite rock in hydrochloric acid and filtration to remove silica impurities. Optimization was achieved using the Box-Behnken design from Design Expert 13.0 software, with temperature (10–50 °C), time (5–10 min), and acid concentration (1–5 M) as variables. Optimal conditions for CaSO4 synthesis were 10 °C, 10 min, and 3.5 M H2SO4. A significant quadratic model (P-value = 0.0002, R2 = 0.923) was developed for CaSO4 synthesis. XRD analysis confirmed the prominent phase angle of synthesized CaSO4 at 11.8° with 92% purity. XRF analysis revealed a composition of 53.686% SO3, and 41.798% CaO. The flaky morphology of CaSO4 was observed from the SEM analysis, and TGA analysis showed stability at 200 °C and decomposition at 383.78 °C. This study demonstrates the suitability of Box-Behnken Design for determining optimal process parameters, and the high-purity CaSO4 produced can be recommended for various applications, including bone implants, plaster of Paris, cement production, and soil remediation.